Gradientes de ph e nutrientes do solo controlam comunidades de anuros em florestas de castanhas da Amazônia Oriental - Santana, Maria Madalena Salviano (Ecologia, 2025)
The Amazon, recognised for harbouring one of the greatest biodiversities on the planet, plays a crucial role in regulating the global climate. Among the groups most sensitive to environmental variations, anurans (frogs, toads and tree frogs) stand out for their high sensitivity. Considering these factors, this dissertation was developed in the Rio Cajari Extractive Reserve, in the state of Amapá, and is structured in two chapters. The first chapter analyses the influence of environmental variables — distance from the stream, vegetation structure, pH and soil nutrients — on the composition and abundance of anurans in rainforests dominated by Brazil nut trees (Bertholletia excelsa). To this end, data collected between January and March 2024 in 24 plots distributed across four 2.5 km transects, using the RAPELD protocol. Anurans were sampled by visual and auditory search at dusk and at night. To collect environmental variables, we used portable terrestrial LiDAR (LTP) to measure vegetation structure, while soil samples were collected for pH and nutrient analysis, and distance from the stream was obtained using geospatial data. The analysis was conducted using manyGLM models (mvabund package) and multiple regressions. Twenty-six species were recorded, notably Allobates femoralis, Adenomera andreae, and Osteocephalus oophagus. The results point to soil pH and nutrients as the main factors structuring the communities, while vegetation structure and distance to the stream had a more limited influence. The second chapter presents an illustrated guide to identifying the recorded species, written in accessible language and aimed at the local communities of the Cajari Extractive Reserve. The material focuses on environmental education, with the aim of supporting conservation actions and promoting sustainable ecotourism in the region. Thus, the dissertation highlights the relevance of edaphic factors in the organisation of Amazonian anuran communities and emphasises the integration between science, environmental education and biodiversity conservation.
Keywords: Fatores Edáfico; Castanhais; pH do Solo